KIAT DALAM MENJAGA KESEHATAN FISIK DAN MENTAL DI MASA PANDEMI BAGI WARGA BINAAN LAPAS KELAS II A PEKANBARU - Devi Purnama Sari; Shelly Angella, R. Sri Ayu Indrapuri, Fitri Andriani, Yoki, Rahmat (JOURNAL OF COMMUNITY DEDICATION, 2022)
Corona virus infection or COVID-19 is caused by coronavirus, which is a group of viruses that infect the respiratory system. In the majority of cases, the coronavirus only causes light to medium respiratory infections like flu. The characteristics of the corona virus at the beginning as though flu symptoms are often underestimated by patients. However, Covid-19 infection runs fast, especially in patients with previous health problems, the corona virus develops rapidly to cause more severe infections and organ failure. Due to the importance of maintaining health during a pandemic, it is also necessary to pay attention to how to prevent the transmission of covid-19 and tips in maintaining physical and mental health during a pandemic, especially in areas where the number of people is crowded but isolated, such as Class Penitentiary (LAPAS) II A Pekanbaru through socialization in the form of seminars. The result of this socialization is hopefully that people around the LAPAS environment can apply tips for maintaining physical and mental health during the pandemic.